Gibberellins, Endogenous and Applied, in Relation to Flower Induction in the Long-Day Plant Lolium temulentum - Pharis, Richard P. (1987)
Changes in endogenous gibberellin-like substances (GAs) and related compounds in the shoot apices of Lolium temulentum during and after flower induction by one long day was examined for plants grown in three consecutive years. The total GA level in the shoot apical tissue was high (up to 42 micrograms per gram dry weight, or 3 × 10(−5) molar GA(3) equivalents), increasing several-fold on the day after the long day and then declining. Of the many GA-like substances present, the putative polyhydroxylated components—with HPLC retention times between those of GA(8) (three hydroxyls) and GA(32) (four hydroxyls), and accounting for about a quarter of the total GA activity—were most consistent and striking in their changes. Their level in the apices increased 3- to 5-fold on the day after the long day and then subsided. When various GAs were applied to plants in noninductive short days, flower initiation was induced by several, most notably by GA(32), GA(5), 2,2-dimethyl GA(4), GA(3), and GA(7). GA(32) was most like one long day in eliciting a strong flowering response while having little effect on stem growth, whereas GA(1) had the opposite effect. It is suggested that highly hydroxylated C-19 GAs may play a central role in the induction of flowering in this long-day plant.